Triple Oral Antithrombotic Therapy in Atrial Fibrillation and Coronary Artery Stenting: Searching for the Best Combination - Elewa, Hazem; Ahmed, Dina; Barnes, Geoffrey D. (Seminars in Thrombosis and Hemostasis, 2016)
Patients with atrial fibrillation (AF) who are treated with oral anticoagulants often have concurrent coronary artery disease. Triple oral antithrombotic therapy (TOAT) is often necessity to prevent stent thrombosis or myocardial infarction associated with percutaneous coronary intervention or acute coronary syndrome in patients with comorbid coronary artery disease and AF. Although the use of TOAT (aspirin, clopidogrel, and warfarin) has excellent efficacy against thrombotic complications, this comes on the expense of increased bleeding risk. This review discusses potential strategies to improve TOAT benefit–risk ratio evidence from the literature. These strategies include: (1) dropping aspirin; (2) reducing the duration of TOAT; (3) switching warfarin to a direct oral anticoagulant (DOAC); (4) the use of DOAC in combination with a single antiplatelet agent; and (5) switching clopidogrel to a novel antiplatelet agent. Although dropping aspirin and reducing TOAT duration should be considered in selected AF patients at low risk of thrombosis, the role of DOACs and novel antiplatelets in TOAT has not been thoroughly studied, and there is limited evidence to support their use currently. Ongoing studies will provide safety and efficacy data to guide clinicians who frequently face the challenge of determining the best TOAT combination for their patients.
Keywords: antithrombotic; antiplatelet; warfarin; atrial fibrillation; acute coronary syndrome